Filthy Lucre? Innovative Communities, Identity, and Commercialization - Mollick, Ethan (Organization Science, 2016)
Online communities play an increasingly important role in developing innovation. However, relatively little is known about the ways in which community affiliation influences how innovations and products generated in these communities are commercialized. By examining open source software (OSS) as an example of an innovation community and using both a quasi experiment and a longitudinal survey, I seek to shed light on this issue. In the quasi experiment, using the launch of the Apple App Store, I find a decreased propensity toward commercialization among individuals associated with online community innovation. I then examine the mechanisms for this decreased commercialization with a novel longitudinal survey of OSS community members. Despite the history of OSS as an anticommercial community, I do not find that anticommercial attitudes play a role in commercialization decisions. Instead, differences in entrepreneurial self-identity have large significant effects on the propensity to commercialize. I conclude with a discussion of the implications of these findings for the literatures on both entrepreneurial identity and community innovation.